EFEKTIVITAS KONSELING KELOMPOK REALITA UNTUK MENGURANGI SISWA KECANDUAN GADGET DI MADRASAH ALIYAH DARUL ULUM WARU - Neni Sumarni; Endang Pudjiastuti Sartinah; Budi Purwoko (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The phenomenon of gadget addiction nowadays is not difficult to find among children. Those who have responsibility have also made efforts to reduce addiction, but it is not sufficient to provide more intensive services. The strategy that can be carried out in this study is using the want, direction, evaluation, planning (WDEP) reality counseling model in a group setting. The research objective was to determine the effectiveness of reality group counseling to reduce students' gadget addiction at Madrasah Aliyah Darul Ulum Waru. Research methods include quantitative, experiments using pretest and posttest. Subjects set 7 students. The selected subject is included in the category of high gadget addiction. Data was collected through gadget addiction instruments, expert tests and trials have been carried out. Data analysis used the Wilcoxon sign rank test.Based on the results of the analysis using the Wilcoxon sign rank test, it was found that z count = -2.936, and z table = 1.96, meaning that z count is greater than z table (-2.936> 1.96), then Ha is accepted meaning effective reality group counseling to reduce students addicted to gadgets at Madrasah Aliyah Darul Ulum Waru.